Strategic analysis of Granit, spol. s.r.o. - Fiala, Adam; Boukal, Petr, 1962-2022; Sieber, Martina; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2017)
This Bachelor's thesis focuses on a strategic analysis of Granit spol. s.r.o., which is an industrial company. The aim of the thesis is to evaluate the situation of the company on the market. Theoretic body describes a methodical process of the strategic analysis and introduces the literature used in the thesis. Practical part applies techniques mentioned in the previous part and introduces the company. Output of the analysis is SWOT analysis, statements about current company situation and general suggestions for future company development.
Vedoucí práce: Petr Boukal
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: podniková ekonomika a management [obor bakal. práce]; bakalářské práce; bachelor's theses